Immediate-early mRNA-2 of herpes simplex viruses types 1 and 2 is unspliced: conserved sequences around the 5' and 3' termini correspond to transcription regulatory signals. - Whitton, J L (1983)
Nuclease S1 and exonuclease VII analyses of immediate-early (IE) mRNA-2 of herpes simplex viruses types 1 and 2 (HSV-1, HSV-2) show them to be unspliced and of similar length. The DNA sequences around the 5' and 3' termini have been determined. Comparison of the sequences around the 5' ends reveals several common features. (1) Four discrete blocks of upstream homology which are precisely colinear with respect to the 5' termini of the mRNAs; the blocks include the 'TATA' box, a G-C rich sequence and a sequence (AATTAAATACAT) which may be involved in the coordinate induction of the IE class of genes. (2) Several copies of the sequence CCCCGCCC, found in different upstream positions in HSV-1 and HSV-2, which may be important in the expression of a wide variety of eukaryotic genes. (3) Potential hairpin structures in the region of the 5' termini which are present at similar locations in HSV-1 and HSV-2. Sequence comparison around the 3' termini of IEmRNA-2 reveals high homology at the proposed C-terminus of the polypeptide.